Estágios imaturos de geometridae (Lepidoptera) associados à Stryphnodendron spp. (Mimosaceae) em área de cerrado no município de São Carlos, SP - Osorio, Tereza Costa (2005)
Geometridae larvae feeding on two Stryphnodendron species were collected twice a month over an year in a cerrado area in São Carlos, SP, Brazil. 1062 larvae were found and reared in laboratory. Fifteen species and ten genera were recorded: Thyrinteina arnobia, Thyrinteina schadeana , Physocleora junctilinea , Iridopsis fulvitincta, Glena unipennaria , Glena subannulata , Glena brachia , Hymenomima amberia , Hymenomima conia, Macaria abydata , Macaria sp., Prochoerodes sp., Patalene sp., Scopula sp. and Leuciris sp. The latter was the most frequent species. A greater number of larvae were found on S. obovatum than on S. adstringens. Nevertheless, larvae feeding in S. adstringens were more likely to be parasitized than those feeding on S. obovatum.152 cases of parasitism were recorded due to Diptera (Tachinidae) or Hymenoptera (Ichneumonidae, Braconidae, Chalcididae e Eulophidae); Euplectrus sp. (Eulophidae) was the commonest parasitoid. The number of collect larvae was related to leafing phenologies and increased during the leaf expansion time.